Nanosheet Zinc Oxide Synthesized by Solution-Immersion Method for Triboelectric Nanogenerator - Suriani Abu Bakar (Tanjung Malim, 2024)
Nanosheet Zinc Oxide Synthesized by Solution-Immersion Method for Triboelectric Nanogenerator by Suriani Abu Bakar